The effect of L-arginine therapy on hepatocyte cells damage in mice (Mus musculus) model of preeclampsia - S Soetrisno; Bambang Arinekso; Sri Sulistyowati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Preeclampsia is one of the main contributors on morbidity and mortality of mother and fetus. Imbalance of body antioxidants and oxidants has a role on endothelial destruction causing endothelial dysfunction which leads to preeclampsia. L-arginine administration is indicated to be able to fix the remodelling process of hepatocytes which was damaged on preeclampsia. The aim of this study was to investigate the effect of L-arginine on hepatocyte cells damage on mouse (Mus musculus) model of preeclampsia. Experimental study was conducted in the Experimental Animal Warehouse and Biomedical Laboratory, Faculty of Veterinary Medicine, Airlangga University, Surabaya. A total of 30 pregnant mice were divided into three groups with 10 mice in each group i.e. normal, preeclampsia model and preeclampsia model with L-arginine therapy pregnant mice. Preparates were taken from dissected mice liver, with prior paraffin block and were then stained with hematoxylin-eosin. Results were analyzed semi quantitatively with Manja Roenigk hepar histology scoring method. Data were analyzed using Kruskal-Wallis and Man-Whitney test. Mean of hepar histopathology score of preeclampsia model with L-arginine therapy (40.80±1.17/µm2) was significantly lower compared with preeclampsia model pregnant mice (58.80±4.23/µm2) (p<0.05), however it was significantly higher compared with normal pregnant mice (18.40±2.41/µm2) (p<0.05). It was indicated that the L-arginine therapy on preeclampsia mouse model can reduce the score of hepar histopathology. In conclusion, L-arginine administration can reduce the hepatocyte cells damage of mouse due to preeclampsia.